2011
DOI: 10.7326/0003-4819-155-3-201108020-00003
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Risk for Complications After Transthoracic Needle Lung Biopsy of a Pulmonary Nodule: An Analysis of Discharge Records

Abstract: Background Because pulmonary nodules are found in up to 25% of patients undergoing chest computed tomography, the question of whether to biopsy is becoming increasingly common. Data on complications following transthoracic needle lung biopsy are limited to case series from selected institutions. Objective To determine population-based estimates of risks of complications following transthoracic needle biopsy of a pulmonary nodule. Design Cross-sectional analysis. Setting The 2006 Healthcare Cost and Utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
268
4
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 420 publications
(298 citation statements)
references
References 16 publications
14
268
4
3
Order By: Relevance
“…A recent study on 15.865 adults who had transthoracic needle biopsy of a pulmonary nodule showed that the risk for any pneumothorax was 15.0% (CI: 14.0-16.0%), and 6.6% (CI: 6.0-7.2%) of all biopsies resulted in pneumothorax requiring a chest tube [15]. On the contrary, we did not insert chest drains but again our experience is small.…”
Section: Discussionmentioning
confidence: 77%
“…A recent study on 15.865 adults who had transthoracic needle biopsy of a pulmonary nodule showed that the risk for any pneumothorax was 15.0% (CI: 14.0-16.0%), and 6.6% (CI: 6.0-7.2%) of all biopsies resulted in pneumothorax requiring a chest tube [15]. On the contrary, we did not insert chest drains but again our experience is small.…”
Section: Discussionmentioning
confidence: 77%
“…Pneumothorax rates have been reported at 0.5%, 4%, and 15% for EBUS-TBNA, transbronchial biopsy and transthoracic needle aspiration, respectively [24,25,10]. In the current study, the number of patients who received EBUS-TBNA was not documented, and therefore the impact on the results is unknown.…”
Section: Discussionmentioning
confidence: 59%
“…Based on a literature review of complications associated with rebiopsy [8][9][10], the data were searched for the following complications: pneumothorax, hemorrhage, bronchial spasms, arrhythmia, severe chest pain, light headedness, trouble breathing, excessive bleeding, hemoptysis, fever, and death.…”
Section: Complicationsmentioning
confidence: 99%
“…[16][17][18] Due to this reason, the American College of Chest Physicians recommends TTNA for lung nodules present without a bronchus sign only when RP-EBUS (radial endobronchial ultrasound) is not available. [13] Although transthoracic needle aspiration is a technically demanding procedure, documented evidence has shown that it is accurate with limited morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] Various groups have shown lower pneumothorax rates for Fluoroscopy guided transthoracic needle biopsies. [14][15][16][17][18] The only drawback of using Fluoroscopy is the risk of exposure to radiation for both patients and radiologists, which can be minimized by using the 'quick check' method. [20,21] Ultrasound guided TTNA biopsies are generally well tolerated probably because lung lesions guided by ultrasounds are peripheral in nature with less chances of pneumothorax.…”
Section: Introductionmentioning
confidence: 99%